The Turndown of Soviet Modernity: from Chernobyl and Ignalina to the Green Movement and Sąjūdis - Baločkaitė, Rasa; Rinkevičius, Leonardas (Sociologija. Mintis ir veiksmas, 2008)
The modern governments are conceived as to draw their legitimacy based on universal rational knowledge and the concept of controllable and calculable risks as a tool for ensuring progress and welfare of society. The multiple risks and uncertainties of modernisation that the governments were incapable to deal with caused a deficit of legitimacy and institutional ambiguity (or the institutional void as Hajer suggested calling it). Consequently, new actors and new political arenas or spaces have emerged and are expected to lead to institutional innovation. The Soviet system represents the version of the modern state which based its legitimacy on the principle of rationalism applicable towards external nature and was challenged by multiple risks and side effects of its industrial development that led to the deficit or even absence of legitimacy. The crisis of legitimacy of the Soviet state and institutional void, this paper argues, was a key premise for the former Soviet republics such as Lithuania to restore its’ statehood and independence in search of new democratic participatory modes of governance. The theoretical perspective based on governance transformations induced by the crisis of legitimacy, uncertainties of modernisation and institutional void in the former Soviet system of governance is illuminated by two empirical cases rooted in the nuclear energy sector, namely the accident at Chernobyl Nuclear Power Plant in Ukraine in 1986, and public controversy around the Ignalina Nuclear Power Plant in Lithuania.
Keywords: soviet modernity; social change; nuclear risk; legetimacy crisis; institutional void; participatory governance